2015
DOI: 10.1007/s11356-015-4818-7
|View full text |Cite
|
Sign up to set email alerts
|

Pb(II), Cr(VI) and atrazine sorption behavior on sludge-derived biochar: role of humic acids

Abstract: Pyrolyzing municipal wastewater treatment sludge into biochar can be a promising sludge disposal approach, especially as the produced sludge-derived biochar (SDBC) is found to be an excellent sorbent for heavy metals and atrazine. The aim of this study was to investigate how and why the coexisting humic acids influence the sorption capacity, kinetic, and binding of these contaminants on SDBC surface. Results showed humic acids enhanced Pb(II)/Cr(VI) sorption binding, and increased the corresponding Pb(II) Lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The strongest suppression occurs for large molecules with reduced access to interior pores, especially when the biochar has been coflocculated with the humic substance. Moreover, Zhou et al (2015) confirmed that pore blockage (confirmed by BET surface area measurement) as well as the more hydrophilic surface with more sorbed water molecules mainly suppressed the sorption of atrazine by biochar. In addition, hydrophobic effects and electron donor acceptor (EDA) might also be responsible for lower chloramphenicol sorption in the presence of humic acid.…”
Section: Effects Of Humic Acid Salt and Soil Concentration On Kdsupporting
confidence: 53%
“…The strongest suppression occurs for large molecules with reduced access to interior pores, especially when the biochar has been coflocculated with the humic substance. Moreover, Zhou et al (2015) confirmed that pore blockage (confirmed by BET surface area measurement) as well as the more hydrophilic surface with more sorbed water molecules mainly suppressed the sorption of atrazine by biochar. In addition, hydrophobic effects and electron donor acceptor (EDA) might also be responsible for lower chloramphenicol sorption in the presence of humic acid.…”
Section: Effects Of Humic Acid Salt and Soil Concentration On Kdsupporting
confidence: 53%
“…Liu et al [ 25 ] found that, when adding 5% (in mass) stalk carbon with particle size of 0.25 mm in paddy soil, available contents of Pb, Zn, and Cu in the soil were reduced by 52.5%, 52.1%, and 50.1%, respectively. Adsorption of heavy metals (such as Cd, Pd, and Cr) usually increased in soil–biochar system due to the increasing sorbed sites for heavy metals which was supplied by the coated DOM (dissolved organic matter) of soil onto biochar [ 26 , 27 ]. In theory, biochar addition can improve the adsorption capacity of degraded soil and reduce the mobility and bioavailability of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, since negatively charged HA and Cr(VI) were simultaneously present in the adsorbent suspension, they might compete to occupy the finite adsorption sites on the Fe 3+ -BC surface, with a lower than expected adsorption of Cr(VI) onto Fe 3+ -BC; [67] Meanwhile, it was considered that HA had a better ability to chelate Fe 3+ -BC, which reduced active sites of Fe 3+ -BC available to Cr(VI); [68] Moreover, HA might form aggregates on the surface of Fe 3+ -BC, which would prevent Fe 3+ -BC from adsorbing Cr(VI); [69] Besides, it has been reported that HA has a high adsorption affinity for Cr(VI), [70] which might prevent the removal of Cr(VI) by reducing the concentration of the available Cr(VI). On the other hand, at low pH values, the negatively charged HA could be easily adsorbed, so the strong complexation of surface adsorbed HA with Cr(VI) should result in the increased adsorption of Cr(VI) on Fe 3+ -BC surface; [71] Furthermore, HA could enhance the removal of Cr(VI) via the adsorption-coupled reduction reaction, which has been widely accepted as the real mechanism of Cr(VI) adsorption through both direct and indirect reduction mechanisms under the acidic conditions. [71,72] In previous studies, thiol, phenolic, carboxylic, methoxy, and carbonyl functional groups in HA structure have been reported as effective electron-donor groups for Cr(VI) reduction.…”
Section: Effect Of Humic Acid On Cr(vi) Removalmentioning
confidence: 99%
“…On the other hand, at low pH values, the negatively charged HA could be easily adsorbed, so the strong complexation of surface adsorbed HA with Cr(VI) should result in the increased adsorption of Cr(VI) on Fe 3+ -BC surface; [71] Furthermore, HA could enhance the removal of Cr(VI) via the adsorption-coupled reduction reaction, which has been widely accepted as the real mechanism of Cr(VI) adsorption through both direct and indirect reduction mechanisms under the acidic conditions. [71,72] In previous studies, thiol, phenolic, carboxylic, methoxy, and carbonyl functional groups in HA structure have been reported as effective electron-donor groups for Cr(VI) reduction. [71] Hence, the presence of HA facilitated the Cr(VI) adsorption at the initial pH of 3.0 primarily by offering more positively charged groups of the adsorbed HA on Fe 3+ -BC surface for Cr(VI) binding and electron-donor groups for Cr(VI) reduction.…”
Section: Effect Of Humic Acid On Cr(vi) Removalmentioning
confidence: 99%
See 1 more Smart Citation